Does the crisis period affect the properties of various financial assets: evidence from G7, BRIC, GCC countries - Marwa Eleuch; Nada Souissi; Mourad Mroua (Cogent Business & Management)
This paper investigates the role of various financial assets as diversifiers, hedges, and safe havens using the dynamic conditional correlation-GARCH and quantile regression models, for the period from August, 10 2015 to June, 5 2024 for the case of G7, BRIC, and GCC countries. Results show that gold’s robust safe-haven status, alongside commodities like oil, gas, and wheat, which exhibit varying degrees of resilience in turbulent market conditions. Our findings identify the G7 and BRIC indices as strong safe havens, contrasting with the clean energy index, which shows limited safe-haven properties during crises. This research provides critical insights into asset behavior under extreme market volatility, offering practical implications for investment strategies and risk management by highlight the strategic decisions for asset allocation during uncertain financial periods.